A New Approach To Estimate The Base Bearing Capacity Of Driven Piles Based On SPT Data - N. Shariatmadari (Deep Foundations Institute, 2006)
In recent years, determining bearing capacity of piles from in-situ testing data as a complement of static and dynamic analysis has been used by geotechnical engineers. In this paper, different approaches for estimating base bearing capacity of piles from SPT data has been compared and evaluated. A new method for pile base bearing capacity in sand is proposed using SPT records. Data averaging, failure zone extension, and plunging failure of piles have been addressed in the proposed approach. A data bank comprising 10 full scale static load tests on instrumented piles and 26 dynamic tests, analyzed with signal matching technique by CAPWAP software, was used for validation. The SPT data that was performed close to pile locations is also included in the data base. Comparison of current methods by error investigation with Log-Normal approach demonstrates that the proposed method predicts pile base capacity with more accuracy and less scatter in comparison to other methods.